Identification of Aspergillus fumigatus UDP-Galactopyranose Mutase Inhibitors - Martin del Campo, Julia S. (Sci Rep, 2017)
Aspergillus fumigatus is an opportunistic human pathogen responsible for deadly, invasive infections in immunocompromised patients. The A. fumigatus cell wall is a complex network of polysaccharides among them galactofuran, which is absent in humans. UDP-galactopyranose mutase (UGM) catalyzes the conversion of UDP-galactofuranose (UDP-Galf) to UDP-galactopyranose (UDP-Galp) and is an important virulence factor. UGM is a flavin-dependent enzyme that requires the reduced flavin for activity; flavin reduction is achieved by reaction with NADPH. The aim of this work was to discover inhibitors of UGM by targeting the NADPH binding site using an ADP-TAMRA probe in a high-throughput screening assay. The flavonoids (2S)-hesperetin and (2S)-naringenin were validated as competitive inhibitors of UGM against NADPH with K(i) values of 6 µM and 74 µM, respectively. To gain insight into the active chemical substituents involved in the inhibition of UGM, several derivatives of these inhibitors were studied. The results show that the hydroxyl groups of (2S)-hesperetin are important for inhibition, in particular the phenyl-chroman moiety. Congo red susceptibility assay and growth temperature effects showed that these compounds affected cell wall biosynthesis in A. fumigatus. This work is the first report of inhibition studies on UGM from eukaryotic human pathogens.